Kajian Komunikasi dalam Sudut Pandang Studi Fenomenologi: Literatur Review - Maulana, Zidan Abid; Budiyono, Alief (Universitas Islam Balitar, 2024)
This article reviews the literature on the application of the phenomenological approach in communication studies. Phenomenology is a method that focuses on exploring individuals' subjective experiences and how individuals make meaning of the communication phenomena they experience. This approach emphasizes the importance of understanding the construction of meaning from the participants' perspective, as well as the social and cultural contexts that influence that meaning-making. The history and basic concepts of phenomenology are discussed, including the thoughts of thinkers such as Edmund Husserl and Alfred Schutz. Key characteristics of phenomenological research such as bracketing, focus on a single phenomenon, small sample, and thematic analysis are also outlined. The study explores the application of phenomenology in examining aspects of communication such as organizational, interpersonal, and media communication. This approach is able to provide in-depth insights into how individuals construct meaning and respond to communication messages in the context of everyday life. Phenomenology is also considered useful in understanding communication experiences shaped by recent social changes and technological developments. The review concludes that phenomenological research in communication can contribute significantly to enriching our understanding of the complexities of human communication interactions and experiences holistically.